Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Energi Di Indonesia - Melisa, Nanda; Oktavianti, Santi; Haqiqi, Teuku Muhammad; Zainal, Rabin Ibnu; Firmansyah, Firmansyah (Journal of Management, Entrepreneur and Cooperative, 2024)
The energy company is a sector company that sells products and services related to energy extraction which includes non-renewable energy so that revenue is directly affected by world energy commodity prices such as oil mining, natural gas, coal. The purpose of this study is to determine whether the capital structure of firm size has an effect on firm value. The analytical method used is panel data regression through eviews 12. With this research the researcher used a purposive sampling data collection technique. Purposive sampling is a sampling technique with a certain determination, with a total population of 37 energy sector companies listed on the Indonesia Stock Exchange 2019-2022, and based on predetermined criteria, a sample of 30 companies from the energy sector in 2019-2022 was obtained. The results showed that the variable capital structure (DER) has a negative effect on firm value, while company size (SIZE) has a positive effect on firm value. Simultaneously capital structure and company size affect company value in Energy sector companies listed on the IDX in 2019-2022. The ability of the independent variables to simultaneously explain the dependent variable can be said to be included in the level of a strong relationship and this research model is good.